A comparison of the brittle PMMA with the ductile PC on the elasticity and yielding from a molecular dynamics perspective. (4th June 2021) - Tang, Zhiye; Fujimoto, Kazushi; Okazaki, Susumu
Abstract: The microscopic stress origins of elasticity and yielding of the brittle poly-(methyl methacrylate) (PMMA) under uniaxial extension condition was studied using a previously proposed method, and compared with ductile polycarbonate (PC). For this brittle material, the same energetic terms, namely, the bond, angle, and van der Waals (vdW) stresses, were identified as the major contributors to the overall stress response before the occurrence of cavitation that precedes the brittle fracture, meaning that the stress is produced under the identical mechanism with the ductile PC. However, all terms for PMMA have larger values, that add up to the overall higher stress, because of the more remarkable bond stretching and angle bending, and the loss of repulsive vdW interaction at even shorter distances between homochain adjacent sidechains than PC. The bulky and dense sidechains of PMMA are responsible for a large portion of the total stress response, and causes the difficulty in their conformational relaxation, and thus can be identified as a key structural reason for the larger elastic modulus and a potential candidate for the causes of its brittleness. This provided an insight into the higher elastic modulus and brittleness of PMMA. Graphical abstract: Image 1 Highlights: Brittle PMMA has the same stress origins of elasticity and yielding as ductile PC. Elastic modulus comes from bond, angle and vdW while vdW shapes yielding. PMMA has larger elastic modulus and cavitates after yielding because of sidechains. The large number of sidechains in PMMA results in its larger elastic modulus. Flexibility reduction by the sidechain "coating" leads to microscopical brittleness.